The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1007/bf00935481
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium derivatives act as growth factor ? mimetic compounds upon differentiation and proliferation of osteoblast-like UMR106 cells

Abstract: The effect of different vanadium compounds on proliferation and differentiation was examined in osteoblast-like UMR106 cells. Vanadate increased the cell growth in a biphasic manner, the higher doses inhibiting cell progression. Vanadyl stimulated cell proliferation in a dose-responsive manner. Similar to vanadate, pervanadate increased osteoblast-like cell proliferation in a biphasic manner but no inhibition of growth was observed. Vanadyl and pervanadate were stronger stimulators of cell growth than vanadate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
1
8

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 28 publications
8
115
1
8
Order By: Relevance
“…UMR106 rat osteosarcoma cells were grown in DMEM containing 10% FBS, 100 U/ml penicillin and 100 μg/ml streptomycin at 37°C in 5% CO 2 atmosphere (Cortizo and Etcheverry, 1995). Cells were seeded on 75 cm 2 flasks and subcultured using trypsin-EDTA.…”
Section: Cell Culture and Spheroid Preparationmentioning
confidence: 99%
“…UMR106 rat osteosarcoma cells were grown in DMEM containing 10% FBS, 100 U/ml penicillin and 100 μg/ml streptomycin at 37°C in 5% CO 2 atmosphere (Cortizo and Etcheverry, 1995). Cells were seeded on 75 cm 2 flasks and subcultured using trypsin-EDTA.…”
Section: Cell Culture and Spheroid Preparationmentioning
confidence: 99%
“…Vanadate was also shown to exhibit strong metabolic and mitogenic effects, as demonstrated by in vitro studies using mammalian bone-derived cell lines (and also using rat calvaria and chondrocyte primary cultures) (Canalis 1985a;Kato et al 1987;Lau et al 1988). These effects have been extensively studied using two mammalian cell lines, MC3T3-E1 and UMR106, and important features, such as tyrosine phosphorylation and activation of signalling mechanisms, have been characterized (Barrio and Etcheverry 2006;Cortizo and Etcheverry 1995;Salice et al 1999). Although repetitively studied in mammals, vanadate effects have not been investigated in marine vertebrates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results have shown that due to the competition of the SO 4 2-ion in the equilibrium, only the first complexed species (ML) could be detected, before the whole system precipitated. These solutions however were investigated by EPR spectrometer in order to measure the A o and g o parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The vanadyl solutions were prepared in two different ways as follows. In the first one, a proper mass of the VOSO 4 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation